Aesthetic Virginity, Ethical Liberty and the Autonomy of Beauty: Possessions and the Poetics of Postcolonialism in the Aspern Papers - Naz, Bushra (Studia Anglica Posnaniensia, 2022)
I argue that The Aspern Papers takes up the question of aesthetic chastity in terms of the unnamed narrator’s pretended courtship of Tina when he was a lodger in her home, through which she finally achieves aesthetic-ethical freedom as a single woman. Like Isabel in The Portrait of a Lady, Tina at first does not appreciate her suitor’s self-interestedness, but then manages to establish her aesthetic-ethical autonomy by rendering her virginal spirit proof against its objectification and exploitation by the lodger, in a Kantian parable of freedom. Juliana’s jealous possession of Jeffrey Aspern’s papers and her imperious guardianship of Tina prompt a sustained exploration of Kantian and Saidian notions of interest and disinterest, in which Juliana’s machinations are generally comparable to Madame Merle’s. Kant’s idea of interest refers to bias in the formulation of aesthetic judgement, lacking the disinterest of a truly dispassionate judgement of beauty. Edward Said’s notion of interest represents imperial prejudice. From these two complementary perspectives, Tina’s struggle to transform her presumed feminine interest in masculine sponsorship allows her finally to attain complete disinterestedness in relation to the sexual, familial, historical, and political forces that press on her. On the other hand, the lodger’s ardent pursuit of Aspern’s private papers, tokens of the poet’s aesthetic achievement, involves an imperial agenda to wrest control of them for his own interest as a man of letters and connoisseur of poetry.